A nurse practitioner–led medication reconciliation process to reduce hospital readmissions from a skilled nursing facility. Issue 2 (February 2020) - Anderson, Rachel; Ferguson, Rita
ABSTRACT: Background and purpose: Skilled nursing facilities (SNFs) are penalized for hospital readmissions within 30 days. Medication errors often precipitate hospital returns. The Centers for Medicare and Medicaid Services mandates that health care providers must determine whether medications pose significant risks and implement corrective actions. Federal restrictions exist regarding nurse practitioners (NPs) in long-term care; however, NPs are efficient in the health care of patients requiring a SNF, including completing thorough medication reconciliation and correcting deficiencies. Local Problem: A needs assessment of a 90-bed SNF revealed inadequate medical coverage and no formalized program to reduce hospital readmissions, including a mandated medication reconciliation process. The problem contributed to an average 30-day readmission rate of 24.15%. Methods: The investigators sought to determine whether an NP-led medication reconciliation on admission would reduce hospital readmissions from a SNF. A pre- and postimplementation design was used to compare 30-day hospital readmission rates over a 30-day project period. Interventions: An evidence-based workflow process for systematic medication reconciliation was designed. A full-time NP used the workflow process to complete stabilization visits with medication reconciliation on each facility admission. Results: Results revealed a hospital readmission rate of 19.2% preimplementation and 13.5% postimplementation, reflecting a 29.7% decrease in the rate of hospital readmissions within a 30-day period. Conclusion: A chi-square analysis conveyed no statistical significance; yet, the positive benefits of NP intervention included reduced hospitalizations, increased revenue, improved quality measures and survey results, and preparation for the Centers for Medicare and Medicaid Services mandates. Implications for practice: Nurse practitioners have the necessary education and skills to provide quality care as well as achieving CMS mandates and improving quality measures in SNF settings.